The relative role of soil, climate, and genotype in the variation of nutritional value of Annona senegalensis fruits and leaves - Donhouedé, Janine Conforte Fifonssi; SALAKO, Kolawolé Valère; ASSOGBADJO, Achille; Ribeiro-Barros, Ana I.; Ribeiro, Natasha (My University, 2023)
Annona senegalensis Pers is a multipurpose tree species valued for food and medicinal uses in Africa. Although there have been attempts to document the proximate composition of fruits and leaves, little is known about the relative role of soil, climate, and genotype on the nutritional quality. The present study evaluated the variation of the proximate composition of fruits and leaves in populations from Benin and Mozambique. It further assessed the impact of soil, climate and genotype on the proximate composition. Data were collected from four populations geneti cally different and analyzed using descriptive statistics, analysis of variance (ANOVA), principal component analysis, redundancy analysis (RDA), and variance partitioning. Results revealed significant variation in the proximate composition of fruits and leaves among the studied pop ulations. Ashes and fibers in fruits, and lipids in leaves were 4.8-fold, 2.5- fold, and 1.25-fold higher respectively, in populations from Mozambique. Fruits moisture and lipids content were rather 1.4-fold and 1.10-fold higher in populations from Benin. Moisture and lipids were respectively 6-fold and 1.27-fold higher in fruits than in leaves, while ashes, fibers and proteins were approximately twice higher in the leaves than in the fruits. Genetic groups, climate and soils were found to influence this variation. All three factors explained 74.4% of the variation of nutritional value of fruits and leaves, 31.9% of which was exclusively due to genetic variation, 2.8% to the interaction of climate and soils, 24.1% to the interaction of soil and genetic variation, and 15.5% to the interaction of all three factors. Our study shows that genetic variation and soil properties better than climate, explain the variation of nutritional value of A. senegalensis fruits and leaves and further provides essential information that could be harnessed in the domesti cation and breeding program of the species for its edible parts.
Keywords: Proximate composition; Variability; Macronutrients; Annona senegalensis